Understanding Patient Web Portal Use: An Exploration of Evaluation and Usability Studies. (September 2017) - Rogers, Michelle L.; Jeanty, Judith
In times of tightening budgets, hospital systems are looking to health information technology (HIT) to be utilized to contain costs while maintaining or improving health outcomes. When considering health disparities, health IT was looked to for possible solutions to achieve those goals. We conducted a focused review of health services and informatics literature to identify how evaluation and usability were described in patient web portals (PWPs) used by medically underserved communities. We conducted a focused review of health services and informatics literature to identify how evaluation and usability were described in the patient portal work as it refers to use by medically underserved communities. In our search, we restricted our review to patient portals that are "tethered" to existing health care institutions as opposed to those that are consumer facing only (e.g. personal health records). We know that EHR use will continue to increase over time, so this study is timely and appropriate. 430 articles met study criteria which included a search of Web of Science, CINAHL and PubMed databases. Search terms included the phrases (and/or variations): *patient portal*, *patient web portal*, "*tethered electronic health record*", "*tethered personal health record*", "*personal health record*", "*patient electronic health record*", "*underserved" or "minority". The resulting articles assessed the impacts of PWPs on clinical, behavioral, or psychosocial outcomes (Table 1). After review by the three authors, 40 articles were selected to describe the landscape of evaluation and usability studies. The majority of the evaluation studies in this review examined the effect of a PWP on clinical outcomes and patient satisfaction. A majority of articles assessing the usability of PWP systems and functions focused on the perspectives of patients and/or health care providers. Both types of studies are valuable in understanding the role PWPs can play in increasing patient engagement, improving outcomes and enhancing patient-provider communication among patients suffering health disparities. What is less clear are methods to mitigate the identified problems and difficulties in the PHR interface design and implementation. There is lack of literature on the differential impacts of organizational structure and support as opposed to individual use and behavior. The attention paid to evaluation and usability offers a unique view into use and usefulness of information technology. Additional approaches are likely to be necessary to understand the underlying cultural and cost concerns. We know that EHR and PWP use will continue to increase over time, so this study is timely and appropriate.